MSSearch: busca semântica de objetos de aprendizagem OBAA com suporte a alinhamento automático de ontologias - Silva, Luiz Rodrigo Jardim da (Universidade do Vale do Rio dos Sinos, 2013)
Semantics heterogeneity problems are becoming an important field of research. Within the educational context, researchers have focused on developing new technologies to improve the processes of localization, retrieval, cataloging, and reuse of learning objects. This scenario highlights the use of ontology alignment techniques to provide integration between different ontologies. Therefore, the goal of the present work is to develop a tool that provides mechanisms for semantic search of learning objects, with support for automatic aligning ontologies.
Keywords: Web semântica; Busca semântica; Ontologias; Alinhamento de ontologias; Objetos de aprendizagem; Sistemas multiagentes; Repositórios semânticos; Semantic web; Semantic search; Ontology alignment; Learning objects; Multiagent systems; Semantic repositories; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação